Community Participation and Subjective Wellbeing: Mediating Roles of Basic Psychological Needs Among Chinese Retirees - Chen, Lanshuang; Zhang, Zhen (Frontiers in Psychology, 2021)
Objectives: Participation in various social organizations, including community organizations, has become an important part of later year. The current study examined the effects of community participation on subjective well-being (SWB) and mediating mechanisms among retired residents. Specifically, this study attempts to explain the link between community participation and SWB from the perspective of basic psychological needs (BPN). Methods: A total of 1458 community-dwelling retirees aged ≥ 50 years in China participated in this study. A self-developed questionnaire measured the general levels of community participation. BPN were assessed with the Basic Psychological Needs Scale. SWB was represented by life satisfaction, positive affect, and negative affect. Results: Community participation positively predicted one’s SWB. Specifically, retirees with a higher levels of community participation often indicated higher life satisfaction and positive affect, and lower negative affect. Three basic psychological needs, which consist of needs for autonomy, competence, and relatedness, mediated the effect of community participation on SWB, respectively, after controlling for some main demographic and socio-economic factors. Conclusion: The BPN perspective provides a comprehensive explanation for understanding the link between community participation and SWB. Policymakers should consider the role of community participation when developing measures to improve retirees’ quality of life.